Application of Q-REST (Qur'an Recitation for Emotional Stress Therapy) for Mothers in Labor: A Case Report - Namira Anfi Normalitasari; Sulastri Sulastri (GLOBAL HEALTH SCIENCE GROUP, 2026)
Childbirth is an experience that has physical, social, and psychological impacts. One of the psychological changes that occur in pregnant women is the emergence of anxiety. The purpose of this case study is to explain the effect of Al-Qur'an murottal therapy in reducing anxiety levels in mothers giving birth. This study used a quasi-experimental method. The research instrument used the Perinatal Anxiety Screening Scale (PASS) questionnaire to evaluate the pre-test and post-test given intervention. The PASS questionnaire has been proven to be valid (validity value 0,4–0,7) and has very good reliability with Cronbach's Alpha 0,98. The data was analyzed descriptively by comparing anxiety scores before and after therapy and then calculating the percentage reduction in anxiety. The results of the PASS scale before the Al-Qur'an murottal therapy at the first meeting with a score of 35 (severe anxiety), while after the Al-Qur'an murottal therapy at the first meeting for 30 minutes obtained a PASS score of 29 (moderate anxiety). At the second meeting the results of the PASS before the Al-Qur'an murottal therapy with a score of 28 (moderate anxiety), while after the Al-Qur'an murottal therapy with a PASS score of 18 (moderate anxiety). This study provides information on how to reduce non-pharmacological anxiety levels with Al-Quran murottal therapy with Surah Ar-Rahman.